A pragmatic analysis of political language in print media / Seerwan Anwer Majeed - Seerwan Anwer , Majeed (2015)
The pragmatic approach is interested in studying the practical language into the use, not the ornate language by the assonance and distant from the spirit of reality. Hence, that language approaches the media language and depends on the easy practical language. The researcher used the descriptive and analytical methodology in his thesis. He tried through this methodology to stand on the deliberative structure to describe, analyze, and then comment on it in the ancient and modern linguistic heritage; to open the bridge of communication with the spirit of the media language, indicating the contribution of two sciences in this field. As well as, the researcher also tried to identify the concepts of pragmatic approach used in Arabic cloth (flavor) through the study of essences of semantic, morphological and compositional levels. Then the researcher wanted to explain this convergence between the linguistic deliberative approach and the political media language through applications to the media evidences found in the language of a newspaper; having a hope to reach the establishment of a building in which he can apply the deliberative approach to the prose language of the press. At the conclusion, the researcher obtained a number of the most notable results that are as follows: 1. The deliberative theories applied to Arabic language cannot be applied by the same approach to the foreign languages. However, Arabic has its own characteristics, as applying this approach to Arabic the essences of its linguistic levels, qualities and characteristics cannot be overlooked. 2. The essence of the media message shares with the core of the pragmatic approach, as the essence of media process represents these questions composed as below: “Who says? What does he say? By using which means? To whom does he speak? Does it has any effect? What is the reaction?” These questions are also confirmed by the deliberative approach making the title of its study "the use of language”. 3. Through living with the linguistic heritage, it became clear to the researcher that they have taken from (the rhetorical sciences, grammar, criticism, and scientific speech in Arabic) a fertile field to put the dimensions of deliberative thinking. 4. Although the works of linguistic scholars were scattered in their own books that had no system, and did not reach to get an identity integrated, but their huge efforts remain always noticeable in the establishment of many of the ideas and principles adopted by Arab deliberative scholars recently, as if they had studied those efforts and not ignored them; may there was no need to these long years of theorizing and rooting for this deliberative approach, even their theories were matured, brighter and the most beautiful today.